Computed tomography and magnetic resonance imaging in cystic fibrosis lung disease - Eichinger, Monika; Heußel, Claus Peter; Kauczor, Hans-Ulrich; Tiddens, Harm; Puderbach, Michael (Journal of magnetic resonance imaging, 2010)
Computed tomography (CT) is the current “gold standard” for assessment of lung morphology and is so far the most reliable imaging modality for monitoring cystic fibrosis (CF) lung disease. CT has a much higher radiation exposure than chest x-ray. The cumulative radiation dose for life-long repeated CT scans has limited its use for CF patients as their life expectancy increases. Clearly, no dose would be preferable over low dose when the same or more relevant information can be obtained. Magnetic resonance imaging (MRI) is comparable to CT with regard to the detection of most morphological changes in the CF lung. It is thought to be less sensitive to detect small airway disease. At the same time, MRI is superior to CT when it comes to the assessment of functional changes such as altered pulmonary perfusion. The recommendation is to further reduce radiation dose related to the use of CT and to use MRI in the follow-up of morphological changes where possible. J. Magn. Reson. Imaging 2010;32:1370-1378. © 2010 Wiley-Liss, Inc.
Gesehen am 02.03.2023